Bahasa Inggris - Gracia Paula Fahik; Sutapa Gusti Ngurah; I Gusti Agung Widagda; Ni Kadek Nova Anggarani; Made Sumadiyasa; I Gde Antha Kasmawan (Postgraduate, University of Mataram, 2025)
A study has been conducted on the Effective Dose of Sensitive Organs and the Risk of Cancer in Contrast to Abdominal CT-Scan Examination to determine the effective dose of sensitive organs and the risk of cancer in male and female patients. This study was conducted at Bali Mandara Hospital, and data was used, namely, 60 CT-scans of the Abdomen in contrast to patient examination data. The sensitive organs of concern in this study are the stomach, colon, bladder, and liver. To determine the effective dose value of sensitive organs, the equivalent dose value (????????) is multiplied by the value (W????) in each sensitive organ. From the calculation results obtained, it is known that the highest dose is received by the stomach and colon with a value of 9.90 ± 3.94 mSv for male patients and 8.82 ± 2.27 mSv for female patients. To find out the cancer risk value in each organ for male and female patients is done by multiplying the equivalent dose value (????????) by the value (rt) in each organ in adult patients. From the results obtained, patients with the highest risk of cancer are male patients with the highest risk, namely the colon organ, with a risk of 79,16 ×10-4 %. From the results obtained, an analysis was carried out to compare the cancer risk in male and female patients for each organ using the Independent T-Test. From the results obtained, it was found that there was a difference in cancer risk between the two patients, where male patients have a greater risk of cancer than women, with the highest average difference in cancer risk, namely 0.00086 ± 0.00066% in the colon organ